Results of the “Paiso” project : Skills work in higher education - Botella Nicolás, Ana María; Hurtado Soler, Amparo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper presents the results of the project The soundscape as an interactive, transversal, and interdisciplinary learning context (PAISO), which was developed during the academic years 2019-2020 and 2020-2021 at the Faculty of Education of the University of Valencia. The participating sample consisted of 748 students from 16 subjects of the Bachelor’s Degrees in Primary and Early Childhood Education and the Master’s Degrees in Secondary Education and the Master’s Degree in Research in Specific Didactics at the University of Valencia and the University of Salamanca, between the two academic years mentioned above.